LANDSCAPE SPHERE OF GEOGRAPHICAL ENVELOPE, ITS POLARIZATION AND MODERN STRUCTURE - V. A. Shalnev; A. V. Lysenko; A. V. Ishkov; E. N. Sutormina (Наука. Инновации. Технологии, 2022)
Introduction. The subject of the research is the evolution of the landscape sphere of the geographical envelope in the civilizational fields of culture of human society, which led to the development of polarization processes of the system «Man-Nature» relationship and to the formation of the evolutionary range of landscapes from primary natural through ethno-cultural to modern cultural. Research in this direction can be used for the development of theoretical and methodological foundations and methods of research of modern landscapes in the framework of evolutionary landscape studies and General geography. Materials and methods of research. This research is based on the key geographic concepts, principles and approaches developed in the Russian geography, considered from the standpoint of evolutionary landscape studies, the doctrines of the geographical envelope, landscape sphere and geographical environment. The most important of them are: the system and geographical approaches, the concept of geographical determinism, the principle of functional polarization of the territory. Research results and their discussion. The evolutionary range of modern structural elements of the landscape sphere is considered on the example of the North Caucasus landscapes, which is a great polygon for the study of modern landscapes, represented by a wide variety. Influenced by the law of zoning in the macroregion of the North Caucasus, polarized modern landscapes are formed in accordance with the modern natural zones allocated by A. G. Isachenko. Conclusions. The study of the complex and diverse spectrum of modern polarized land- scapes of the Earth requires geographers to return to a holistic perception of geographical reality and geographical thinking in the context of new geography using a comprehensive set of paradigms and concepts of General geography. Because it is impossible to understand the complex mosaic of the modern landscape sphere (natural, social, economic, cultural and other issues) and the features of the living environment in which modern humanity lives without the participation of geographers. Moreover, it is impossible to successfully address the issues of sustainable development of society. At the same time, the concept of geographical determinism, which has always been inherent in geography, should play an important role here.